A Presumptive Case of Human Rabies: A Rare Survived Case in Rural Ghana - Apanga, Paschal Awingura; Awoonor-Williams, John Koku; Acheampong, Michael; Adam, Matthew Ayamba (Frontiers in Public Health, 2016)
Rabies remains endemic in Ghana and continues to pose a major public health threat to humans and animals with a nearly 100% case fatality rate in humans. We report of a presumptive case of human rabies whose survival represents a rare occurrence in rural Ghana and worldwide. Lessons from this case study provide a critically needed focus in helping improve rabies surveillance and case management in Ghana. We report of the survival of a 36-year-old man who developed clinical rabies after he was bitten by his dog, while restraining the dog with a chain. Prior to this, he did not observe any abnormal or rabid behavior in the dog. Following the bite, he did not immediately resort to hospital treatment, but rather to traditional application of herbs to the laceration he sustained after the bite. The reason given for not seeking immediate hospital treatment was that the dog was not rabid and lack of funds to seek hospital care. However, after 10 days he began to show symptoms of confusion, hydrophobia, and photophobia, consistent with rabies virus infection, and was subsequently rushed to the hospital by relatives. At the hospital, he was administered human immune tetanus immunoglobulin, diazepam, ceftriaxone, paracetamol, and intravenous fluids. No rabies vaccine was administered. Six days after commencing treatment, the patient became well, showed neither signs of confusional state, hydrophobia, nor photophobia. He was discharged home after 13 days of commencing treatment. This study provides insight on a presumptive case of human rabies that survived despite non-administration of rabies vaccine after exposure. It also exposes the weaknesses in the health and veterinary systems in rural Ghana regarding rabies surveillance and case management.